Path loss model for indoor emergency stairwell environment at millimeter wave band for 5G network - Al-Samman, Ahmed Mohammed; Rahman, Tharek Abd; Hindia, Mhd Nour; Nasir, Jamal (Scientific and Technological Research Council of Turkey (TÜBİTAK), 2018)
The unused millimeter-wave (mmWave) spectrum offers a superb opportunity to increase mobile broadband capacity due to the enormous amount of available bandwidth. Different candidate operating frequencies for 5G wireless networks are available at the mmWave band. For 5G wireless networks, the emergency case is one of the applications. This paper presents the outcome of indoor emergency stairwell measurement campaigns for 5G system at 26 GHz, 28 GHz, 32 GHz, and 38 GHz, which were conducted at the University Technology Malaysia, Kuala Lumpur, Malaysia. To effectively evaluate the performance of 5G wireless systems in these different bands, single- and multifrequency path loss models are proposed for this environment. This paper proposes a new path loss model based on a new physical anchor point referred to as physical-anchor stair (PAS) path loss model. In a single-frequency large-scale case study, the PAS and the floating intercept (FI) path loss model are investigated at the 20 GHz and 30 GHz bands. Moreover, this study is extended to cover the multifrequency path such as the alpha, beta, and gamma model and the close-in free space path loss model with frequency weight (CIF) model. The CIF model is developed in this paper. The proposed PAS model shows high accuracy (physically based model) and less complexity compared with the studied models. Results show that the path loss exponent values vary between 6.6 and 7.9 for all measured frequencies using the proposed PAS model and between 9.1 and 10.9 using the FI model.